Redox modification of cell signaling in the cardiovascular system - Shao, Dan (2011)
Oxidative stress is presumed to be involved in the pathogenesis of many diseases, including cardiovascular disease. However, oxidants are also generated in healthy cells, and increasing evidence suggests that they can work as signaling molecules. Intracellular reduction-oxidation (redox) status is tightly regulated by oxidant and antioxidant systems. Imbalance between them causes oxidative or reductive stress which triggers cellular damage or aberrant signaling, leading to dysregulation. In this review, we will briefly summarize the aspects of ROS generation and neutralization mechanisms in the cardiovascular system. ROS can regulate cell signaling through oxidation and reduction of specific amino acids within proteins. Structural changes during post-translational modification allow modification of protein activity which can result in alteration of cellular function. We will focus on the molecular basis of redox protein modification and how this regulatory mechanism affects signal transduction in the cardiovascular system. Finally, we will discuss some techniques applied to monitoring redox status and identifying redox-sensitive proteins in the heart.